Network Flexibility and Policy Making in Software Defined Networks - Sharma, Abhinav; Sood, Manu (Discoveries in Agriculture and Food Sciences, 2015)
Today’s computer networks are complex which is very challenging to manage as well as these traditional networks struggle to scale to the requirements of some of today’s environment. SDN gives solution to all these requirements with new dynamic networking features that enhance server value and user services. SDN supplements traditional networking by offering much flexibility and software centric control creating a more policy based process for adding intelligence into today’s networks. Traditionally tweaking a policy/network configuration, network administrators typically rely on a combination of manual intervention and ad-hoc scripts. In this paper we have made an attempt to show how SDN is more robust and provides users flexibility to program the network according to their needs and requirements. We have used KINETIC – a domain specific language and SDN controller to write our priority based switching application.